2020
DOI: 10.3390/foods9060754
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Inclusion of Chestnut (Castanea sativa Miller) in the Finishing Diet and Cooking Technique on the Physicochemical Parameters and Volatile Profile of Biceps femoris Muscle

Abstract: The aim of this study was to evaluate the influence of the diet (chestnut vs. commercial feed) and cooking techniques (roasting, grilling, frying and microwaving) on the quality of the Biceps femoris muscle of the Celta pig breed. Chemical composition, physicochemical parameters, oxidative stability and volatile profile were analysed. Overall, the inclusion of chestnuts did not affect the chemical composition, except for intramuscular fat content, which was higher in chestnut-fed pigs. The colour and shear for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…At the same time, these findings are consistent with those obtained for muscles of Iberian pigs, where it was observed that pigs supplemented with feeds that had a higher content of antioxidant compounds showed greater antioxidant capacities [ 48 , 61 ]. In addition, these aftermaths agree with those obtained in a previous study of our research group, where it was observed that the inclusion of chestnut in the finishing diet of Celta pigs increased lipid oxidation of Biceps femoris muscle cooked through different culinary techniques compared with the muscles of pigs fed with commercial feed [ 86 ]. This fact could be justified with the findings of the present investigation, meaning it is seen that tissues of pigs fed commercial feed has a higher TPC and higher antioxidant activities.…”
Section: Resultssupporting
confidence: 91%
“…At the same time, these findings are consistent with those obtained for muscles of Iberian pigs, where it was observed that pigs supplemented with feeds that had a higher content of antioxidant compounds showed greater antioxidant capacities [ 48 , 61 ]. In addition, these aftermaths agree with those obtained in a previous study of our research group, where it was observed that the inclusion of chestnut in the finishing diet of Celta pigs increased lipid oxidation of Biceps femoris muscle cooked through different culinary techniques compared with the muscles of pigs fed with commercial feed [ 86 ]. This fact could be justified with the findings of the present investigation, meaning it is seen that tissues of pigs fed commercial feed has a higher TPC and higher antioxidant activities.…”
Section: Resultssupporting
confidence: 91%
“…On this matter, the use of volatile compounds as feeding biomarkers to distinguish between commercial and grass-fed animals are of particular relevance because some of these substances have previously been related to specific diets (Almela et al, 2010;Echegaray et al, 2020;Gravador et al, 2015;Lorenzo et al, 2013Lorenzo et al, , 2014Sivadier et al, 2010). This occurrence is due to the fact that several volatile compounds can be transferred to animal tissues directly from the diet (Vasta et al, 2010) or they can appear as a consequence of their generation from certain characteristic substances of the feed.…”
Section: Introductionmentioning
confidence: 99%
“…YU et al found that heat treatment causes a series of changes in meat proteins, including structural (denaturation of sarcoplasmic protein and myofibrillar protein) and molecular (protein carbonylation, modification of aromatic residues, generation of Maillard reaction products) changes [30], which affect the moisture, juiciness, color, etc., of meat. Previous studies indicated that the increase in fat content of meat samples after cooking can be attributed to cooking oil usage, such as in pan-frying and deep-frying [31]. It may also vary between raw materials.…”
Section: Effect Of Different Processing Methods On the Nutritional Qu...mentioning
confidence: 99%